Temporal trend in the nutritional status of children in a Brazilian metropolis in light of food and nutrition policies - Navarro de Azevedo, Luiza; de Oliveira Gallo, Caroline; Constante Jaime, Patrícia; Galastri Baraldi, Larissa (Archivos Latinoamericanos de Nutrición (ALAN), 2024)
Introduction. Brazil’s health system offers insights into addressing the double burden of malnutrition by proper population monitoring, coupled with local policies and national guidelines. Objective. To investigate the recent temporal trends in nutritional status indicators and its coverage of children aged two to five years from Campinas, a metropolis in the state of São Paulo, Brazil. Material and methods. The analysis of time series from 2018 to 2022 were conducted by accessing data from the Brazilian Food and Nutrition Surveillance System (SISVAN) due to regression analysis. Results. The number of children aged two to five in the SISVAN registry rose from 7,300 in 2018 to 11,171 in 2022, forming the study sample. In 2018, 700 were chronically undernourished, 306 underweight, and 977 overweight; by 2022, 530 showed stunting, 457 were underweight, and 1,084 overweight. Stunting prevalence declined from 9.6% (2018) to 4.7% (2022). Underweight dropped slightly from 4.2% to 4.1% over the years and overweight, consistently the highest indicator, ranged from 13.4% (2018) to 9.7% (2022). SISVAN’s coverage varied between 16.6% (2018) and 26.1% (2022), the lowest at 12.3% in 2020. The trend for stunting decreased significantly (APV: -15.01; CI95% -22.64; -6.62). Adding SISVAN’s coverage variable the model slightly reduced the declining stunting trend (APV: -12.12; CI95% -13.19; -11.04). Conclusions. Coordinated efforts to address nutritional challenges, from adequate population monitoring to the interaction between local policies and national guidelines, have shown positive health outcomes. Introducción. El sistema de salud de Brasil ofrece conocimientos valiosos para abordar la doble carga de malnutrición mediante el seguimiento adecuado de la población y políticas locales y nacionales. Objetivo. Investigar las tendencias temporales recientes en indicadores nutricionales y cobertura en niños de dos a cinco años en Campinas, São Paulo, Brasil. Materiales y métodos. Se analizaron datos del SISVAN de 2018 a 2022 con regresión temporal. Resultados. Niños de dos a cinco años en el SISVAN pasaron de 7,300 en 2018 a 11,171 en 2022. En 2018, 700 estaban crónicamente desnutridos, 306 con bajo peso y 977 con sobrepeso; en 2022, 530 con retraso en el crecimiento, 457 con bajo peso y 1,084 con sobrepeso. La prevalencia del retraso en el crecimiento bajó de 9,6% a 4,7%. El bajo peso disminuyó levemente del 4,2% al 4,1% y el sobrepeso osciló del 13,4% al 9,7%. La cobertura de SISVAN varió de 16.6% a 26.1%, con un mínimo de 12.3% en 2020. La tendencia del retraso en el crecimiento disminuyó significativamente (APV: -15.01; CI95% -22.64; -6.62). La inclusión de la cobertura de SISVAN redujo levemente esta tendencia (APV: -12.12; CI95% -13.19; -11.04). Conclusiones. Coordinar esfuerzos para abordar los desafíos nutricionales, desde el seguimiento de la población hasta políticas locales y nacionales, ha tenido resultados positivos para la salud.